The "Forgotten Lands": An Institutional Analysis of Post-Soviet Transitions. Issue 2 (3rd April 2018) - Malyshava, Liudmila
Abstract: This article provides an institutional critique of the analysis of the post-Soviet transition. It seeks to demonstrate that (i) an absence of a thorough institutional analysis, (ii) unrealistic marketization programs, (iii) conflicting ideological perceptions for the role of the state, and (iv) persistent systemic problems of state planning have constituted significant constraints to the transition away from the Soviet style planned organization of production and distribution. Preservation of the Soviet mode of production, in turn, inevitably led to a fundamentally flawed policy approach and guided the former Soviet bloc toward an unproductive and damaging path-dependence. This path-dependence contributed to retarding the process of cumulative causation and capped the influx to the joint stock of knowledge, both of which remain crucial for progressive institutional adjustment.